Estudio de la recuperación de metano en capas de carbón del sinclinal de barruelo - Pinoargote Rovello, César Iván (2011)
The aim of this project is making a study of the coal bed methane production at the Barruelo Synclinal. To achieve that aim, we used PETREL program to create a geological model of the coal layer with the petrophysic properties, fluid characteristics and initial conditions at the Barruelo Synclinal. With ECLIPSE 300 reservoir simulator, we made a forecast of the methane and water production for different separation distance between injection wells, getting those 400 meters separation, according to the methane production and CO2 injected storage, is the indicated option. Finally, we perform a methane production economic study, using the most indicated separation between wells, getting the best profitability for a 10000 m3 of CO2 injection in 7 years of production.